Pre-treatment of thermoduric spores in CO2 modified atmosphere and their survivability during food extrusion - Fraiha,Marcos (2011)
The aim of this experiment was to evaluate how susceptible spores become to mechanical damage during food extrusion after being submitted to CO2. B. stearothermophilus spores sowed to corn and soy mix were submitted to 99% CO2 for 10 days and extruded in a single-screw extruder. The treatments were: T1 - spore-containing samples, extruded at screw rotational speed of 65 rpm and barrel wall temperature of 80 °C; T2 - as T1, except for screw rotational speed of 150 rpm; and T3 - as T2, except that samples were submitted to the modified atmosphere. The results for cell viability, minimum and maximum residence times, and static pressure were T1 - 19.90 ± 3.24%, 123.3 ± 14.50 seconds; 203.3 ± 14.05 seconds; 2.217 ± 62 kPa; T2 - 21.42 ± 8.24%, 70.00 ± 5.77 seconds; 170.00 ± 4.67 seconds; 2.310 ± 107 kPa; and T3 - 11.06 ± 2.46%, 86.00 ± 7.23 seconds; 186.00 ± 7.50 seconds; 2.403 ± 93 kPa, respectively. It was concluded that the extrusion process did reduce the cell count. However, screw rotational speed variation or CO2 pre-treatment did not affect cell viability.